The Way of the Warrior: Business Tactics and Techniques from History's Twelve Greatest Generals - James F. Dunnigan; Daniel Masterson (New York St. Martin's Press, 1997)
A look at military history and leaders including Napoleon, Ghengis Khan, Julius Caesar, Douglas MacArthur, and Norman Schwarzkopf reveals management strategies that can be used in a business context today. 25,000 first printing.
Age Group: Adult
Includes bibliographical references (p. [197]) and index.
"A Thomas Dunne book."
Keywords: Business; Management; Leadership; Success in business; Militarism; History; Leadership; Management; Militarism; Success in business